'Impossible Groups that Flourish in Leaking Containers'—Challenging Group Analytic Theory?. (December 2016) - Weinberg, Haim
All group therapy textbooks emphasize the importance of the setting for a successful outcome of the group. This setting includes clear boundaries of time and space, stable participation, and good leadership. All are seen as requirements to create a safe enough environment for participants to work on deep issues. In addition, for its normal development and progress, the group is expected to go through a stormy stage with disagreements and conflicts. My article will highlight groups that do not follow such 'rules'. Surprisingly, the members are still able to work at deep levels, create intimate relationships, and benefit from the group. How is this possible? Should we change our theories? I link the success of these groups to the secure presence (Neeman-kantor, 2013, researching outdoor groups of wives of Israeli soldiers who suffer from war PTSD) of the leader and the imagined internalized group that the members create. Applying field theory explains how a multi-unconscious-fantasy makes these impossible groups possible.